2015
DOI: 10.1002/clc.22451
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Absorb Bioresorbable Vascular Scaffold: A Systematic Review

Abstract: Bioresorbable stents are novel devices designed to overcome the long‐term limitations of permanent stent implantation. The Absorb bioresorbable vascular scaffold (BVS; Abbott Vascular, Santa Clara, CA) was the first bioresorbable stent with Conformité Européenne mark approval in coronary vessels and has been the subject of multiple clinical studies. Despite its potential advantages, the safety and efficacy of BVS remain unclear. To address this, we conducted a systematic review to examine the safety and effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Featuring less thrombosis risk, the biodegradable DESs have recently been employed as the standard choice for percutaneous coronary intervention (PCI). [25][26][27][28][29] Stent fracture is a high-incidence clinical entity with potential conduction to multiple complications, resulting in serious recurrent angina, myocardial infarction, and even sudden death. [15][16][17][18][19][20] The disadvantages have led to the develpment of fully degradable DESs that are fabricated entirely from biodegradable polymers without any metallic backbones.…”
Section: Wwwadvancedsciencenewscom Wwwadvtherapcommentioning
confidence: 99%
See 1 more Smart Citation
“…Featuring less thrombosis risk, the biodegradable DESs have recently been employed as the standard choice for percutaneous coronary intervention (PCI). [25][26][27][28][29] Stent fracture is a high-incidence clinical entity with potential conduction to multiple complications, resulting in serious recurrent angina, myocardial infarction, and even sudden death. [15][16][17][18][19][20] The disadvantages have led to the develpment of fully degradable DESs that are fabricated entirely from biodegradable polymers without any metallic backbones.…”
Section: Wwwadvancedsciencenewscom Wwwadvtherapcommentioning
confidence: 99%
“…[21][22][23][24] Despite resolving the adverse clinical effects of the remaining metallic backbones, the recent designs could not completely fix the fracture and deployment issues due to the inherent mechanical weakness of conventionally adopted biodegradable polymers. [25][26][27][28][29] Stent fracture is a high-incidence clinical entity with potential conduction to multiple complications, resulting in serious recurrent angina, myocardial infarction, and even sudden death. [16,[30][31][32][33] Autopsy studies have demonstrated fracture incidence of 29% in patients, which often cannot be diagnosed and thus express themselves as severe clinical situations.…”
mentioning
confidence: 99%
“…The rate of target-lesion revascularization ranges from 1 % to 3.3 % after BRS implantation [3, 4]. The most often used method for the treatment of in-scaffold restenosis is a drug-eluting stent (DES) [5], but there is no sufficient data supporting this approach, and the optimal treatment strategy is still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomised clinical trials and meta-analyses have outlined the usefulness of BVS for coronary revascularisation, [11][12][13] although the clinical benefit for ACS patients has not been well analysed. [14,15] The objective of our study was to report the safety and utility of BVS compared to other stents in a cohort of ACS patients.…”
Section: ]mentioning
confidence: 99%